A TSN traffic scheduling algorithm combined with enqueue shaping - Wenxuan HAN; Hailong ZHU; Xinxin HE; Yanjue LI; Changchuan YIN (物联网学报)
Most of the existing studies on the scheduling of mixed traffic in time-sensitive network (TSN) focus on how to ensure low-latency of stream reservation (SR) traffic.However, SR traffic blocks best-effort (BE) traffic for a long time will lead to excessive delay in BE traffic, which is not conducive to the state maintenance of network and the management of system.In order to reduce the maximum end-to-end delay of BE messages, a traffic scheduling algorithm which combines with enqueue shaping was proposed.It reduced the blocking of BE traffic by reducing the reserved bandwidth of SR traffic.The algorithm first added enqueue buffers in front of SR queues.Then, the reserved bandwidth ratio among the same priority traffic was adjusted by setting the number of frames in each enqueue buffer entering the SR queue during enqueue shaping.Finally, it jointed egress shaping to reserve bandwidth resources for each SR flow to match its latency requirement.Simulation results showed that combining enqueue shaping can reduce the maximum end-to-end delay of BE messages by 9.66%～75.76%.